Results of screening for antibodies to varicella-zoster virus in healthcare workers of a multidisciplinary hospital in Moscow - Nataliya M. Afonina; Irina V. Mikheeva; Marina I. Korabelnikova; Zinaida S. Rodionova; Artem V. Snitsar; Sergey N. Perekhodov; Svetlana V. Smetanina; Alexey V. Tutelyan; Stanislav N. Kuzin; Vasily G. Akimkin (Журнал микробиологии, эпидемиологии и иммунобиологии, 2024)
Introduction. Given the unfavorable epidemic situation with chickenpox and shingles in Russia, there is a high risk of virus introduction and spread in healthcare settings, including among medical staff who are not immune to varicella zoster virus (VZV).